2021
DOI: 10.1080/00472778.2020.1865539
|View full text |Cite
|
Sign up to set email alerts
|

Performing and unperforming entrepreneurial success: Confessions of a female role model

Abstract: Female role models are increasingly used in enterprise support to encourage women to open businesses. Although varied in detail, their public narratives generally follow a limited number of plots where hard work overcomes all obstacles and leads to emotionally fulfilling, rewarding careers while societally enabled resource accumulation and financial returns are rarely mentioned. This autoethnographic inquiry critically examines one such publicly disseminated role model narrative, the author's own, and contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 86 publications
0
4
0
1
Order By: Relevance
“…Besides that, Adesola et al (2019) argue that role models can motivate student entrepreneurial involvement. This is substantiated by the findings of Marks (2021), who found that the real-life story of an entrepreneur (role model) is an effective strategy for teaching individuals new to entrepreneurship about entrepreneurship. Next, Bosma et al (2012) demonstrated a significant positive relationship between role models and entrepreneurship, as role models serve as "icons" for startup entrepreneurs, motivating, inspiring, and supporting their entrepreneurial pursuits.…”
Section: Discussionmentioning
confidence: 77%
“…Besides that, Adesola et al (2019) argue that role models can motivate student entrepreneurial involvement. This is substantiated by the findings of Marks (2021), who found that the real-life story of an entrepreneur (role model) is an effective strategy for teaching individuals new to entrepreneurship about entrepreneurship. Next, Bosma et al (2012) demonstrated a significant positive relationship between role models and entrepreneurship, as role models serve as "icons" for startup entrepreneurs, motivating, inspiring, and supporting their entrepreneurial pursuits.…”
Section: Discussionmentioning
confidence: 77%
“…in the service industry versus the technology industry) because of industry characteristics such as life cycle, growth potential and competition. Moreover, role models in the family and social networks can also influence the familial support provided to women entrepreneurs (Austin and Nauta, 2016; Marks, 2021; Nowiński and Haddoud, 2019). Indeed, in settings featuring successful entrepreneurs who serve as role models in the family and/or other social circles, family members may provide more support to women business owners as they may consider their venture to be a family tradition and/or part of their culture.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Previous literature confirmed that female entrepreneurs could not advertise their products; therefore, they are limited to a particular market around them (Islam et al, 2021;Kumar & Shukla, 2019). According to previous literature (Yusuf & Ibrahim, 2021;Kimathi et al, 2020), women entrepreneurs in developing countries are far behind, and as a result, they remain to fail to get maximum benefits from advanced technologies, use of modern equipment, awareness of modern business tools (Marks, 2021;Lim et al, 2021;Okechukwu, & Nwekwo, 2020). If the women adopt these newly developed technologies, they will get enormous benefits in terms of their personal economic and financial benefits.…”
Section: Hypothesized Direct Relationshipmentioning
confidence: 99%